Omipalisib reduces hyperphosphorylated tau protein by modulating mTOR-autophagy pathway - Haeun Hwang; Namkwon Kim; Subyn Jeon; Yoojin Lee; Jeongmin Son; Seung Ho Jeon; Yeongae Lee; Min Sung Gee; Kyung-Soo Inn; Jong Kil Lee (PLoS ONE, 2026)
Tauopathies are neurodegenerative diseases characterized by the presence of hyperphosphorylated tau (p-tau) and neurofibrillary tangles. Autophagy is a critical self-degradation mechanism that preserves cellular homeostasis and function, including the clearance of misfolded proteins. Autophagy is impaired in tauopathies, resulting in excessive accumulation of p-tau. Omipalisib, a dual phosphatidylinositol 3-kinase/mammalian target of rapamycin (PI3K/mTOR) inhibitor, was explored in a phase I clinical trial involving solid tumors and lymphoma. In this study, we aimed to investigate the effects of omipalisib on tauopathy both in vitro and in vivo . Omipalisib increased the levels of protein LC3B and decreased that of p62 in human tau (P301L)-expressing SH-SY5Y stable (SH-Tau) cells by inhibiting mTOR activation in a time-dependent manner. In our study, we hypothesized that omipalisib, a PI3K/mTOR inhibitor, could remove accumulated tau and inhibit memory decline by activating autophagy. Additionally, omipalisib reduced tau phosphorylation in SH-Tau cells without inducing cytotoxicity. Upon administration of 6-month-old PS19 mice with omipalisib (1 mg/kg) for 2 months, the levels of both RIPA-soluble and RIPA-insoluble p-tau were decreased, and spatial memory dysfunction was alleviated in omipalisib-treated PS19 mice. Overall, these results show that omipalisib decreases the expression of p-tau by modulation mTOR-autophagy pathway, resulting in the amelioration of spatial memory deficits. This study highlighted the potential of omipalisib as a candidate treatment for tauopathies.